Sequence–structure–function studies of tRNA:m(5)C methyltransferase Trm4p and its relationship to DNA:m(5)C and RNA:m(5)U methyltransferases - Bujnicki, Janusz M. (Oxford University Press, 2004)
Three types of methyltransferases (MTases) generate 5-methylpyrimidine in nucleic acids, forming m(5)U in RNA, m(5)C in RNA and m(5)C in DNA. The DNA:m(5)C MTases have been extensively studied by crystallographic, biophysical, biochemical and computational methods. On the other hand, the sequence–structure–function relationships of RNA:m(5)C MTases remain obscure, as do the potential evolutionary relationships between the three types of 5-methylpyrimidine-generating enzymes. Sequence analyses and homology modeling of the yeast tRNA:m(5)C MTase Trm4p (also called Ncl1p) provided a structural and evolutionary platform for identification of catalytic residues and modeling of the architecture of the RNA:m(5)C MTase active site. The analysis led to the identification of two invariant residues that are important for Trm4p activity in addition to the conserved Cys residues in motif IV and motif VI that were previously found to be critical. The newly identified residues include a Lys residue in motif I and an Asp in motif IV. A conserved Gln found in motif X was found to be dispensable for MTase activity. Locations of essential residues in the model of Trm4p are in very good agreement with the X-ray structure of an RNA:m(5)C MTase homolog PH1374. Theoretical and experimental analyses revealed that RNA:m(5)C MTases share a number of features with either RNA:m(5)U MTases or DNA:m(5)C MTases, which suggested a tentative phylogenetic model of relationships between these three classes of 5-methylpyrimidine MTases. We infer that RNA:m(5)C MTases evolved from RNA:m(5)U MTases by acquiring an additional Cys residue in motif IV, which was adapted to function as the nucleophilic catalyst only later in DNA:m(5)C MTases, accompanied by loss of the original Cys from motif VI, transfer of a conserved carboxylate from motif IV to motif VI and sequence permutation.